2018
DOI: 10.1097/aud.0000000000000581
|View full text |Cite
|
Sign up to set email alerts
|

Head Movements Allow Listeners Bilaterally Implanted With Cochlear Implants to Resolve Front-Back Confusions

Abstract: Bilateral implantation can offer CI listeners the ability to track dynamic auditory spatial difference cues and compare these changes to changes in their own head position, resulting in a reduced rate of front-back confusions. This suggests that, for these patients, estimates of auditory acuity based solely on static laboratory settings may underestimate their real-world localization abilities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
49
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(59 citation statements)
references
References 31 publications
7
49
3
Order By: Relevance
“…The results of the Pastore et al [27] study indicate that when NH listeners did not move their heads they were almost 100% correct in accurately localizing the six sound sources for the HF filtered noise, and therefore there were almost no FBRs (Fig. 4A).…”
Section: Sound Source Localization By Cochlear Implant (Ci) Patientsmentioning
confidence: 90%
See 1 more Smart Citation
“…The results of the Pastore et al [27] study indicate that when NH listeners did not move their heads they were almost 100% correct in accurately localizing the six sound sources for the HF filtered noise, and therefore there were almost no FBRs (Fig. 4A).…”
Section: Sound Source Localization By Cochlear Implant (Ci) Patientsmentioning
confidence: 90%
“…The four panels (A, B, C, and D) of Fig. 4 (based on Pastore et al [27]) display confusion matrices (i.e., the loudspeaker location reported by listeners as a function of the location of the actual loudspeaker presenting a sound). In the top row listeners (Fig.…”
Section: Sound Source Localization By Cochlear Implant (Ci) Patientsmentioning
confidence: 99%
“…FBC errors are not simply outliers with extreme error amplitudes. The underlying cause is different from normal localization errors (see Figure 1) which is why FBCs should be analyzed seperately [3]- [7].…”
Section: Sound Source (A)mentioning
confidence: 97%
“…In horizontal sound localization experiments, the most common definition classifies responses crossing the interaural axis as FBCs [3]- [6], [8], [9]. This definition, which defines the FBC Rate, is sufficient for experiments that only require a coarse angular resolution of the test setup or feedback method [7], [10], [11]. However, such setups limit the measurement resolution for sound localization accuracy.…”
Section: Sound Source (A)mentioning
confidence: 99%
“…In addition to more comprehensive insight into the localization ability of the subjects, this approach enables the evaluation of FBCs. For broadband noise stimuli in the free field, Makous & Middlebrooks (1990) found average rates of FBCs for 6% of the stimuli, Pastore et al (2018) found 5% and Best et al (2010) reported FBC occurrences of 5%. In this study, we observed FBCs in only 3.6% of the stimuli.…”
Section: Sound Source Localizationmentioning
confidence: 97%